Power Consumption Analysis and Evaluation of Energy Saving Potential of Lighting System in DEF Building - Wardhana, Alex Sandria Jaya; Zamtinah; Sukisno, Toto; Yuniarti, Nurhening; Bachrun, Muhammad Al Azis (Jurnal Edukasi Elektro, 2025)
This study aims to analyze power consumption and evaluate the potential energy savings of the lighting system in the DEF Building, which has various room functions including offices, laboratories, meeting rooms, and libraries. The study was conducted with a descriptive quantitative approach based on field measurement data. Data collection includes measuring lighting intensity (lux), inventory of types and number of lamps, and power consumption (watt). The measurement results were compared with the Indonesian National Standard SNI 6197:2020 to assess the minimum lighting level and maximum power limit. In addition, a simulation of replacing conventional lamps with LED lamps was carried out using Dialux Evo software. The results showed that most rooms had power consumption per square meter that was still efficient (<12 W/m²), but many rooms did not meet the minimum lighting standards. The simulation of replacing lamps with LEDs resulted in significant power savings, with a total reduction in energy consumption of 928.93 kWh per month or equivalent to electricity cost savings of around Rp1,362,997.48. Replacing lamps was also able to improve the quality of lighting in rooms that previously did not meet the standards. This study shows that effective lighting system management through LED lamp retrofitting can be an important strategy in supporting building energy efficiency.